Microplastics in Landfill Environments: Distribution, Characteristics, and Risks from Gampong Jawa, Indonesia - Silvia, Ika; Saiful, Saiful; Ichwana, Ichwana (Graduate School of Universitas Syiah Kuala, 2024)
Landfills are generally considered the ultimate solution for waste management. However, the degradation process of plastic waste in landfills causes the release of microplastic particles into the surrounding environment and threatens human health. The distribution and properties of microplastics in four environment matrices, soil, leachate, river water, and well water surrounding the landfill, are examined in this study. Sampling was conducted at the inflow and outflow areas of the leachate ponds., The soil at the top (05 cm) and bottom (520 cm), upstream and downstream surface water adjacent to the landfill, and community wells within a radius of fewer than 700 meters from the landfill. Microplastic analysis used a gradual extraction method with saturated NaCl for density separation, 30% hydrogen peroxide for organic matter degradation, and 0.05 M FeSO4 as a catalyst. Physical character identification of microplastics using a microscope showed microplastic contamination at all study sites. The results showed an abundance of microplastics was found in well water samples (808 to 979 items/L), leachate (209 to 757 items/L), surface water (6.29 to 7.2 items/L), and soil (23,340 to 23,420 items/kg). Types of microplastics found consist of fragments, fibers, films, pellets, foam, and rods. The size of microplastics found ranged from 1.897 m to 1,642.79 m. Fourier Transform Infrared spectroscopy examination identified polyethylene terephthalate (PET) plastic compounds in soil and leachate materials. The high concentration of microplastics in well water indicates potential groundwater contamination from landfill activities that may impact the surrounding community. This study provides preliminary insights into how landfills may contribute to environmental microplastic contamination. It paves the way for further research to develop mitigation strategies.